Urf Review of The Practice of Gold Marriage Mahar in The Community of Tanjung Senang District Bandar Lampung - Efrinaldi, Efrinaldi; Jayusman, Jayusman Jayusman; Shafra, Shafra; Nurfatati, Nurfatati (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This study aims to reveal and analyze the practice of marriage dowry in the form of gold in the people of Tanjung Senang District, Bandar Lampung in the perspective of 'urf. The method used in this research is a descriptive analytical field research. Primary data in the form of interviews with the community in Tanjung Senang District, Bandar Lampung, then supplemented with secondary data. The results of this study indicate that: the tradition of the people of Tanjung Senang District, Bandar Lampung, it appears that the dowry in a marriage must be in the form of gold, whereas in Islamic law the form of the dowry is not determined in marriage, everything that has value can be used as a dowry. For the people here, dowry other than gold is considered unusual, the tradition of dowry in the form of gold is inherent, this tradition is considered good, it does not conflict with Islamic law, and brings benefit to society in general. This tradition is a form of love and affection, sincerity, and responsibility for the prospective husband to his prospective wife. The nominal is related to the level of education, social status, ethnicity, and profession based on the agreement of the parties. The conclusions of this study are: in the perspective of Islamic law, by referring to the rules of urf, that is to see the traditions/customs that have been attached to the community, and to see the philosophy of the practice of giving dowry as a form of appreciation for the social status of a woman, with the practice of giving this dowry is to achieve a benefit between the two prospective brides and even between large families, then it is not against Islamic law.